The Role Of Financial Education To Financial Capability And Financial Management : Surakarta Students Analysis - Marchelia Puspita Sari; Liana Mangifera (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This study aims to examine the influence of financial capabilities consisting of attitudes, behaviors, and knowledge on financial management mediated by financial education among students in Surakarta. The research method uses a quantitative approach with Structural Equation Modeling (SEM) Partial Least Square (PLS) analysis. Data was collected through an online survey by distributing a Google Form link. There were 170 respondents studied from various universities in Surakarta and most of them came from management and accounting departments. The results of the analysis show that financial education, financial skills consisting of attitudes, behavior and knowledge have a positive and significant effect on financial management, while financial education is successful in partially mediating the influence of attitudes, behavior and knowledge on students' financial management. The implication of these findings is that financial material has an influence on students in managing their finances, especially in terms of frugality and savings. Therefore, college student needs to know and apply the meaning of personal financial management to be able to become students who are good at managing finances and living more prosperously in the future.